Optimization of vehicle automatic navigation path based on remote sensing and GIS - Lu, Wei; Wu, Mingguang (Optik (Stuttgart), 2022)
Taking a general view of the continuous convenience of modern social life, according to the rapid development of traffic network and communication network, this paper studies the vehicle path optimization problem. This paper attempts to design a set of optimal vehicle path from the five aspects of algorithm development stage, algorithm solution idea, data storage mode, analysis data format and algorithm search strategy. According to the relevant theory of urban vehicle path, a mathematical model of vehicle path problem with time window restriction is constructed. Aiming at this model, a*, hierarchical algorithm, ant colony algorithm and genetic algorithm are used Line analysis and discussion, and according to the relevant algorithm examples in the literature to verify the model and algorithm. It is concluded that the combination of a*, ant colony algorithm and genetic algorithm is more suitable for the optimization of vehicle routing, and the hierarchical algorithm, road quality, congestion and other real-time traffic obstacles are improved to establish the vehicle routing optimization system in the traffic network and communication network. During the experiment, five road networks of different sizes were used successively. The modulus of these road networks increased sequentially, and the ratio of the number of road sections to the number of road network nodes was about 1698. And the conclusion drawn through experimental verification and algorithm verification proves the reliability and effectiveness of the system, has certain application value, and promotes the development of society.